Impact of temperature fluctuations on gut histology of the cricket frog, Fejervary alimnocharis (Anura: Dicroglossidae) - Rahman, MM (Journal of Bio-Science, 2016)
Context: Research work was conducted on Impact of temperature fluctuations on gut histology of the cricket frog, Fejervary limnocharis (Anura: Dicroglossidae). Objectives: To understand relationship between histological structure and physiological activities as per periodic life styles of the cricket frog. Materials and methods: The specimens were collected from different parts of Bangladesh. The basic structure of gut of this frog species were comprised of four layers, viz., serosa, muscularis mucosa, submucosa and mucosa in general. Results: The study revealed that the temperature has immense effect on gut structure of F. limnocharis. Muscularis mucosa was wanting in esophagus whereas serosa was the thinnest layer in stomach and intestine in low temperature, 0.02 mm ±0.01 and 0.01 mm ±0 respectively. Astonishingly muscularis mucosa was measured as the thickest layer in esophagus in high temperature, 3.2 mm ±0.2, instead of mucosa, 3.1 mm ±0.152753, which was the thickest layer in stomach and intestine, 2.6 mm ±0.2 and 1.9 mm ±0.450925 respectively. All the layers of gut responded positively to the raised temperature. From this study it can be concluded that temperature fluctuation followed by changes in physiological activities, as in hibernation, may influence the histological structure. J. bio-sci. 22: 15-20, 2014